International Efforts to Protect Cultural Property under International Humanitarian Law - Amani Mohammed Ahmed Issa (International Journal of Law Research and Studies, 2026)
This research explores "The Protection of Cultural Property under International Humanitarian Law". Its significance lies in addressing the systematic destruction of human heritage and bridging the gap between legal texts and field realities. The study aims to consolidate international protection rules, evaluate the role of specialized organizations, and clarify the mechanisms of criminal accountability for violations. Adopting a descriptive-analytical approach, the researcher divided the study into four sections covering the concepts of International Humanitarian Law, cultural property, protection mechanisms, and the liability arising from attacks. The research concluded that heritage protection has become a peremptory international norm, despite political obstacles hindering judicial prosecution. The study recommended aligning national legislation with international conventions and activating universal jurisdiction to ensure no impunity and to preserve human memory.
Keywords: International Humanitarian Law; Cultural Property; Hague Convention 1954; International Criminal Responsibility